All That Is Holy: The Role of Religion in Postcapitalist Communities. Issue 4 (1st October 2020) - Wittrock, Jon
Abstract : Inspired by the works of Marx and Engels, this essay addresses the role of religion in postcapitalist communities by adopting a Wittgensteinian understanding of religion as a series of elements held together by family resemblances rather than a monolithic entity with a core essence. It analyzes proposals concerning both the content of religion, in terms of needs and functions, and also the potential form of religion, in terms of the degree of voluntary cooperation and the extent to which practices are open to continuous reinterpretation and transformation. The essay concludes that it would be desirable to retain many elements commonly considered as core components of "religion"—including collective rituals, sacred sites and symbols, metanarratives, and altered states of consciousness—but consciously transformed and organized in a framework characterized by voluntary cooperation and an openness to continuous transformation that is comprehensive in range and adapting to the shifting cultural and power-political contexts of the communities in question.